PENGARUH CORPORATE SOCIAL RESPONSIBILITY TERHADAP HARGA SAHAM PERUSAHAAN PERBANKAN DI INDONESIA (Studi Empiris pada Perusahaan Perbankan yang terdaftar di Bursa Efek Indonesia tahun 2009 - 2011) - Sapto Bayu Aji (Akademi Akuntansi YKPN Yogyakarta, 2015)
CSR is a company's commitment to improve the well-being of the community through the wisdom business practices and contributions of resources of the company. The study aims to determine the impact of CSR which is expressed by spending funds on the reaction of investors in the capital market. This study examines whether the Corporate Social Responsibility (CSR) with several control variables has an influence on the company's financial performance. Financial performance is proxied with the company's stock price. Using data of annual financial statements and sustainability reports banking companies listed in Indonesia Stock Exchange from 2009 to 2011, the study reports that CSR has a relationship and positive effect on company's stock price. Keywords: Corporate Social Responsibility, Stock Price, and Banking.